Handbook of psychology and sexual orientation - Patterson, Charlotte; D'Augelli, Anthony R. (New York ; Oxford : Oxford University Press, 2013)
An authoritative summary, 'Handbook of Psychology and Sexual Orientation' is the primary resource for the many researchers including a new generation of investigators, who are continuing to advance understanding in this field. Volume editors Charlotte J. Patterson and Anthony R. D'Augelli, along with other leading experts, contribute an extraordinary review of contemporary psychological research and theory on sexual orientation in their specific fields of work.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Includes index.
Keywords: Sexual orientation -- Psychological aspects; Age (Psychology); Bisexuals